Hamstring injury patterns in professional male football (soccer): a systematic video analysis of 52 cases - Gronwald, T.; Klein, C.; Hoenig, T.; Pietzonka, M.; Bloch, H.; Edouard, P.; Hollander, K. (British Journal of Sports Medicine, 2022)
Abstract